Investigation of the copper effect on the mechanical properties of iron-based molibden, nickel and copper powder metals - Somunkiran, Ilyas; Çelik, Halis (My University, 1999)
In this study, new alloys were improved by adding Copper in to Fe-based Mo, Ni and C powder alloys in order to obtain higher strength and toughness. These powder alloys are used mainly in the automotive industry, home aleinses and keys. In this study the effect of copper content on the mechanical properties of these powder alloys was investigated. In the experiments only the copper content was changed under constant compacting and sintering conditions. The tensile and compressive strength of the sintered specimens were determined, the densities were found and the microstructures were examined with optical microscope.
Demi?r esasli moli?bden, ni?kel, bakir katkili toz metal alaşimlarinin mekani?k özelli?kleri?ne bakir oraninin etki?si?
Ulusal Toz Metalurjisi Konferansi: Second National Powder Metallurgy Conference -- 15 September 1999 through 17 September 1999 -- Ankara -- 62638
Keywords: Density; Powder metallurgy; Sintering